Plan de negocios para la creación de un centro de acondicionamiento físico inclusivo para personas con discapacidad físico motora: Lesión medular, sacrolumbar y distrofia muscular - Aguirre Burgos, César Andrés (2018)
Sport and health have a correlation with each other, Ecuadorian sports have had a great growth in recent years thanks to government is contribution and support, with the creation of laws that protect them and is also strengthened with people is aim in making a physical activity, whichever generates sports practice, health and well-being. Ecuador is policies have been focused on social assistance with the creation of inclusive entities and laws which ensure that each member of the society participates in an equal way in social, cultural, political, educational, and sports activities, among others; that is why, today an inclusive environment is generated in public and private sectors. Based on the aforementioned, this business plan is based on the creation of an inclusive fitness center for people with physical motor disability: lumbar sacral spinal cord injury and muscular dystrophy, with which is expected to obtain inclusive results within society. To determine the feasibility of the project, different research methods have been carried out. Analyzing external factors of industry to which business belongs, a PEST, PORTER and EFE matrix analysis was used. Within market research, two types of analysis were carried out, the first of them quantitative with surveys focused in sports consumers and qualitative with interviews with experts and focus groups. Additionally, with industry is results and client's analysis, market and consumer is preferences were known, starting with designing a logo which adds personality to the brand and generating different marketing strategies that allow the client consume the service, likewise it was carried out a financial evaluation which allows to see how profitable the business is. After analyzing the market, industry and finances, it has been concluded that the business is viable, that it has great acceptance among interested persons, that it is financially profitable, with which it is possible to have a good growth and investment return.